Metabolic Syndrome and Associated Factors in a Population-Based Sample of Schoolchildren in Colombia: The Fuprecol Study - Garcia-Hermoso, A (Mary Ann Liebert Inc., 2016)
Background: In contrast to the definition of metabolic syndrome (MetS) in adults, there is no standard definition of MetS in pediatric populations. We aimed at assessing the differences in the prevalence of MetS in children and adolescents aged 9-17 years using four different operational definitions for these age groups and at examining the associated variables. Methods: A total of 675 children and 1247 adolescents attending public schools in Bogota (54.4% girls; age range 9-17.9 years) were included. The prevalence of MetS was determined by the definitions provided by the International Diabetes Federation (IDF) and three published studies by Cook et al., de Ferranti et al., and Ford et al. In addition, we further examined the associations between each definition of MetS in the total sample and individual risk factors using binary logistic regression models adjusted for gender, age, pubertal stage, weight status, and inflammation in all participants. Results: The prevalence of MetS was 0.3%, 6.3%, 7.8%, and 11.0% according to the definitions by IDF, Cook et al., Ford et al., and de Ferranti et al., respectively. The most prevalent components were low high-density lipoprotein cholesterol and high triglyceride levels, whereas the least prevalent components were higher waist circumference and hyperglycemia. Overall, the prevalence of MetS was higher in obese than in non-obese schoolchildren. Conclusions: MetS diagnoses in schoolchildren strongly depend on the definition chosen. These findings may be relevant to health promotion efforts for Colombian youth to develop prospective studies and to define which cut-offs are the best indicators of future morbidity. © Copyright 2016, Mary Ann Liebert, Inc..